REALITY DISTORTION OF CHINESE AND JAVANESE ETHNIC IN ADIT DAN SOPO JARWO CARTOON ANIMATION FILM - Risang Endra Satria; Dr. Hapsari Dwiningtyas, S.Sos, MA (Interaksi Online, 2016)
Adit dan Sopo Jarwo is a cartoon animation film which represent cultural diversity of ethnic groups that exist in Indonesia. This study aimed to describe the reality distortion gainst ethnic Chinese and Javanese featured in Adit dan Sopo Jarwo film. This study also wants to reveal the ideology and values of the dominant contained in the film. The theory used include the representation theory of Stuart Hall, the theory of Public Opinion Walter Lippman, Antonio Gramsci's theory of hegemony, as well as some related concepts such as marginalization, meaning fashion and body language in the film. Data were analyzed using analysis of John Fiske television code. The results showed that the text of the mass media, especially Adit dan Sopo Jarwo cartoon animation film distorting the reality of the ethnic Chinese and Javanese. Text animated cartoons showing feudalism of the Chinese community as well as the marginalization of ethnic Javanese. Distortion of reality at the level of the reality of marginalized ethnic Javanese, in particular through the elements of body language, expression, background, and style of speaking. At the level of representation, distortion of reality appears in the narrative element, conflict, dialogue, and characterization. Both of these levels to clarify the Javanese into the non-dominant. Distorted reality at the level of reality, favor ethnic Chinese. Ideology of feudalism offered by the media, which displays that ethnic Chinese are the ones who are always right, and the Javanese persons subject to the ethnic Chinese. In addition, the dominance of the ideology of Islam as a conflict resolution strategy also appears in the text of the film. The conclusion of this study indicate that the reality distortion is inevitable in the representation in the mass media, especially movies. Then the media in representing the ethnic diversity is expected to not only see from a partial truth, but rather shows the elements of ethnic identity in a more comprehensive and diverse. This research can be a reference for other researchers who discuss about ethnicity, stereotypes, and media representation, particularly media animated cartoons.